2004
DOI: 10.1111/j.2042-7166.2004.tb04557.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of guided imagery as an adjuvant cancer therapy

Abstract: SUMMARYAim: The aim of this paper is to summarise and critically evaluate the evidence available from controlled clinical trials regarding the use of guided imagery as a sole adjuvant therapy for cancer patients.Methods: Electronic searches for controlled clinical trials were carried out in eight databases and two clinical trial registers. Trials that featured guided imagery as a sole adjuvant therapy were included. No language restrictions were imposed. Data were extracted and validated independently by two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
(30 reference statements)
1
30
0
2
Order By: Relevance
“…Further RCTs were sought via review reference lists [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The systematic review was limited to results from English-speaking samples to minimise problems in generalising results across languages and cultures.…”
Section: Systematic Review Strategymentioning
confidence: 99%
“…Further RCTs were sought via review reference lists [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The systematic review was limited to results from English-speaking samples to minimise problems in generalising results across languages and cultures.…”
Section: Systematic Review Strategymentioning
confidence: 99%
“…[8][9][10] These images are typically visualized with the goal of evoking a state of relaxation, possibly with a specific outcome in mind (eg, pain relief). 8 GI was suggested to be an effective treatment for pain in a variety of clinical conditions 11,12 and is said to modulate the immune system, 13 deactivate the neuroendocrine system, 7,14,15 and facilitate mind-body healing. 16 An earlier systematic review of GI concluded that "the data seem sufficiently encouraging for the use of GI as an adjuvant cancer therapy."…”
mentioning
confidence: 99%
“…These interventions aim at providing patients with knowledge and skills to cope with and achieve personal control over their symptoms, 18 and take advantage of the principle that by learning how to focus the mind it is possible to control the emotions and the bodily functions. Some mind-body interventions used as complementary therapy have been shown beneficial effects for controlling the clinical, emotional, behavioral, and spiritual disorders associated with cancer and its therapy, including relaxation, 19 guided imagery, 20 yoga, 21 tai chi, 22 qigong, 23 and meditation. 15 Meditation encompasses an array of techniques and procedures that have in common the focusing of attention either on breathing, visualizations, and mantras, or on the practitioner's own thoughts.…”
mentioning
confidence: 99%